Why Returning to VET? Results of a Qualitative Comparative Study about English and German Car Mechatronics - Gericke, Erika Edith (International Journal for Research in Vocational Education and Training, 2017)
Educational choices, especially the influence of class on these choices have been a subject of lively international debate. However, thus far, there has been little international and comparative research with respect to vocational and education training (VET) decision making from a subject-oriented perspective. This paper considers occupational-biographical orientations of English and German car mechatronics and focuses on the roles of learning and gaining vocational qualifications. Drawing on the concept of occupational-biographical orientations, the paper describes three types of orientations based on analyses of findings from 11 autobiographical-narrative interviews with English and German car mechatronics. The interviews clearly showed that occupational-biographical orientations explained different views on the necessity of returning to (continuous) vocational education and training. They also demonstrated that subjective perceptions of the national VET system fostered particular occupational-biographical challenges, which supported or hindered existing learning attitudes. Overall, the findings suggested that occupational-biographical orientations exerted the most important influence on learning biographies and decisions to return to (continuous) VET.